Real-life experiences with galcanezumab disclosed new predictors for response - Yalınay Dikmen, Pınar; Baykan, Betül; Uludüz, Derya; Özge, Aynur; Ilgaz Aydınlar, Elif; Polat, Burcu; Karlı, Necdet; Tepe, Nermin; Ertaş, Mustafa (SAGE Publications Ltd, 2023)
[Abstract Not Available]
Keywords: Galcanezumab; New Predictors; Experiences